Generation of the functionally enhanced proximal tubular cells from human iPSC-derived kidney organoids - Sua Kim; Sun Ah Nam; Jin Won Kim; Jawoon Yi; Jin Ju Woo; Minji Lee; Jeongeun Lee; Tae-Hyung Kim; Hyunglae Kim; Hyung Wook Kim; Jiwhan Park; Yong Kyun Kim (Experimental & Molecular Medicine, 2026)
Abstract Human renal proximal tubular epithelial cells (RPPTCs) are crucial for exploring the molecular and cellular mechanisms underlying the pathophysiology of kidney injuries. In this study, we generated the functionally enhanced kidney organoid-derived proximal tubule cells (FEKOPTCs) from human induced pluripotent stem cells. Heparan sulfate proteoglycans and transforming growth factor-β receptor inhibitor enhanced the functionality of PTCs isolated from the kidney organoids of which the vascularization and maturation were improved by heparan sulfate proteoglycans and vascular endothelial growth factor. FEKOPTCs showed significantly enhanced epithelial barrier function, polarization state, and transporter function, compared with primary human RPTECs, which led to improve the function of drug uptake. Transcriptomic characterization of FEKOPTCs revealed high similarity to PTCs of native human adult kidney. FEKOPTCs-on-chip are more sensitive predictors than RPTECs-on-chip for nephrotoxicity testing. By using CRISPR−Cas9 genetic mutation of alpha-galactosidase A, the causative gene of Fabry disease, alpha-galactosidase A-mutant FEKOPTCs, recapitulated the functional phenotype of Fabry disease. When FEKOPTCs were transplanted into the kidney parenchyma of NOD-SCID mice, they reassembled and regenerated proximal tubular structures with intact lumens and functional transporters. Taken together, our results suggest that FEKOPTCs are functionally enhanced PTCs and can be applied for nephrotoxicity testing, disease modeling, and regenerative medicine.